2021
DOI: 10.1111/bld.12436
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the Personal Relationship Advisory Group in a community learning disability service: A service development project

Abstract: Accessible summary The project aimed to explore discussions from the Personal Relationship Advisory Group (PRAG) meetings in a community adult learning disability team to influence the development of new relationship resources. All meeting minutes within a 12‐month period were analysed to find themes. The themes suggest the importance of the service looking at the whole person, such as their physical, emotional and social well‐being, when there are relationship concerns. New resources that focus on personal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Both raters reached the same ratings for the two independently rated studies. Eight qualitative studies were assessed as being of high quality (Bates et al, 2021;Finlay et al, 2015;Franklin & Smeaton, 2018;Franklin et al, 2019;McElearney et al, 2021;Pryde & Jahoda, 2018;Wilkinson et al, 2015), and two of moderate quality (Coleman & Sharrock, 2022;Malovic et al, 2018). The high-quality studies were observed to have clear aims and rationale for qualitative methodology, the findings were presented clearly, and the research was deemed highly valuable.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Both raters reached the same ratings for the two independently rated studies. Eight qualitative studies were assessed as being of high quality (Bates et al, 2021;Finlay et al, 2015;Franklin & Smeaton, 2018;Franklin et al, 2019;McElearney et al, 2021;Pryde & Jahoda, 2018;Wilkinson et al, 2015), and two of moderate quality (Coleman & Sharrock, 2022;Malovic et al, 2018). The high-quality studies were observed to have clear aims and rationale for qualitative methodology, the findings were presented clearly, and the research was deemed highly valuable.…”
Section: Search Resultsmentioning
confidence: 99%
“…Malovic et al (2018) did not sufficiently justify the need for a qualitative methodology and was not observed to have analyzed the data rigorously. Coleman and Sharrock (2022) were not observed to have provided detailed considerations of ethical issues, and elements of the design were not adequately justified. It is also worth noting that 4 out of the 10 qualitative studies did not report on the relationship between researcher and participants (Bates et al, 2021;Franklin et al, 2019;McElearney et al, 2021;Wilkinson et al, 2015).…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The global pandemic and impacts of lockdown highlighted the importance of people with learning disabilities having access to technology and the internet [ 2 , 35 ]. Online safety has long been a concern for people with learning disabilities themselves as well as families and carers [ 36 ]. We can see this reflected in the British Journal of Learning Disabilities where two of the top five most cited articles focus on internet usage both with the terms ‘risks’ in their titles [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%